UPAYA MENINGKATKAN HASIL BELAJAR SISWA MENGGUNAKAN METODE PEMBELAJARAN DISCOVERY LEARNING DENGAN MATERI SISTEM KOLOID SISWA KELAS XI - Nugrohaini, Fitri; Suyana, Iyon; Rahmat, Nahzim; Wijayanti, Sukma Wahyu (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Terbuka, 2023)
The problem discussed in this study is how to improve learning outcomes and student learning activities using the discovery learning method with colloidal system material for class XI MIPA SMA IT Istiqomah Temanggung. This study aims to improve the learning outcomes and learning activities of XI MIPA SMA IT Istiqomah Temanggung students about colloidal system material using discovery learning methods. The research data were obtained from 18 students in class XI MIPA SMA IT Istiqomah Temanggung. When the research was conducted in semester 2 of the 2022/2023 school year. This classroom action research was conducted for 2 cycles. The collection of material understanding data was measured by understanding tests and student learning activities were measured by observing student learning activities. Data analysis was grouped based on data on students who were able to achieve KKM on student learning outcomes and learning activities. The Minimum Completeness Criteria (KKM) for chemistry subject class XI is 70. The learning outcomes of students in cycle 1 who achieved KKM were 7 students (39%). In cycle 2 there was an increase in student learning outcomes to 15 students (83%) who achieved KKM. Student learning activities consist of 3 aspects, namely the aspect of discussion ability, learning interaction and presenting the results of the discussion. From the observations of student learning activities in cycle 1, there were 7 students (39%) who achieved KKM scores. In cycle 2 student learning activities increased to 18 students (100%) who achieved KKM scores.